Related Factor Analysis and Nursing Strategies of Diarrhea in Critically Ill Patients with Enteral Nutrition. (21st September 2022) - Liu, Donglian; Liu, Qinghong; Wen, Xiansong
Abstract : Objective . To explore the related factors of diarrhea in critically ill patients with enteral nutrition (EN) in the intensive care unit (ICU). Methods . This single-center retrospective study analyzed the occurrence of intolerant diarrhea in ICU patients receiving EN treatment in our hospital. By collecting clinical data, univariate and multivariate logistic regression analysis was used to screen the risk factors for diarrhea. Results . Among 120 patients included in the study, 68 (48.33%) had diarrhea. Age (OR = 2.599, P = 0.027 ), use of antibiotics (OR = 3.496, P = 0.007 ), ICU hospitalization time (OR = 1.311, P = 0.001 ), and mechanical ventilation time (OR = 1.273, P = 0.035 ) were all independent risk factors for diarrhea in EN. Conclusion . Older age, frequent use of antibiotics, long ICU stay, and mechanical ventilation time can lead to diarrhea in ICU patients receiving EN treatment. It is necessary to effectively analyze the above independent factors and implement targeted interventions to improve the incidence of diarrhea in patients.